Assessing the Benefit of a Digital Pain Alert System in a Community Hospital - Grosman-Rimon L; Jorgoni L; Casey J; Tory S; Kumbhare D; Solanki J; Collins BE; Wegier P (Journal of Pain Research)
Liza Grosman-Rimon,1 Linda Jorgoni,1 Jane Casey,2 Susan Tory,1 Dinesh Kumbhare,3 Jhanvi Solanki,1 Barbara E Collins,1 Pete Wegier1,4 1Humber River Health, Research Institute, Toronto, Canada; 2Tampa General Hospital, Tampa, FL, USA; 3Department of Medicine, Division of Physical Medicine and Rehabilitation, University Health Network, Toronto, Canada; 4University of Toronto, Institute of Health Policy, Management and Evaluation University of Toronto, Toronto, CanadaCorrespondence: Liza Grosman-Rimon, Humber River Health, 235 Wilson Ave, North York, Toronto, ON, M3M 0B2, Canada, Tel +1416-242-82109, Email l.grosman@hrh.caIntroduction: In the last decade, clinical alert systems were developed for clinical use, including patient deterioration and other urgent clinical situations. However, investigations focusing on digital pain alert systems to assess and manage pain on time in in-hospital patients are scarce. The objective of the study was to assess the implementation of digital pain alerts in the various departments of a community hospital.Methods: Administrative data from the year 2020 to 2023 were collected. Only data from cases when pain alert was activated were included. Data included pain alert activation frequency, pain alert response duration (time from pain alert activation to alert stop when medication was administered), the department from which the pain alert was activated.Results: There was a steady significant decrease in the mean pain alert response duration over time from 2020 to 2023. The department with the shortest pain alert response duration was the Department of Surgery, and Cardiology (252.76 ± 4.712). The longest time delay was in the ICU (463.27± 2.73 min) and at the Mental Health Department (440.59± 5.46 min) (p < 0.01). The pain alert response duration gradually decreased from 2020 to 2023, with decreases from the first year in all of the units/departments, except for the ICU. NPS scores at the start of the alert to 30 minutes after alert stop decreased significantly.Conclusion: Management of pain improved over time across the hospital, and in most of the departments, suggesting that with experience, digital pain alert systems have the potential to improve pain management by providing timely pain intervention.Keywords: digital pain alert, community hospital, pain management, command centre